The prevalence and distribution of hypodontia inorthodontic patients in Bosnia and Herzegovina (Journal of Health Sciences, 2024)
Introduction: The need for this study on the prevalence of hypodontia in a sample of orthodontic patients from Bosnia and Herzegovina arises from the fact that in the state of Bosnia and Herzegovina, there is a lack of data on the prevalence and distribution of hypodontia as a previously defined, growing global problem and that it could emphasize the importance of its early diagnosis, as this is still the best standard for preventing the occurrence of complications due to a lack of teeth. The aim of this retrospective study was to determine the prevalence and distribution of hypodontia in orthodontic patients in Bosnia and Herzegovina.Methods: The study was conducted in the Orthodontic Department of the University of Sarajevo, Faculty of Dentistry, with the Center for Clinical Dentistry. The study included all patients who presented to the Orthodontic Department in the period from January 2020 to March 2023 and whose diagnostic protocol included panoramic radiographs, which were analyzed for the purposes of this study. The sample consisted of the orthopantomography radiographs of 5084 patients (2031 males and 3053 females).Results: Hypodontia was found in 6.77% of orthodontic patients, of which 38.4% were male patients and 61.6% were female. The teeth most frequently affected by hypodontia were the second premolars (68.15%). After stratifying the sample by jaw, the most common hypodontic tooth was the second premolar in the mandible and the lateral incisor in the maxilla.Conclusion: We can conclude that the prevalence of hypodontia in orthodontic patients in Bosnia and Herzegovina and its distribution are very similar to the general population. The results of this study may help to improve the early diagnosis of hypodontia as a growing problem, which may reduce the complications that may arise from missing a tooth.